Discovering potential bioactive compounds from Tualang honey - Chew, Chee Yung; Chua, Lee Suan; Soontorngun, Nitnipa; Lee, Chew Tin (Agriculture and Natural Resources, 2018)
Tualang honey is well known for its biological activities including as an antioxidant and anti-inflammatory. The compounds contributing to the biological activities are still unknown. Therefore, fractionation was carried out to prepare phenolic-rich extract from Tualang honey using ethyl acetate (EA). EA could recover a wide range of phenolic compounds obtained using column chromatography (CC) and liquid-liquid extraction (LLE) after acid hydrolysis. The yield of the EA fraction from LLE (0.83%) was higher than that from CC (0.39%). The LLE-EA fraction also contained more metabolites, especially organic acids (gluconic acid, succinic acid, hydroxybenzoic acid, hydroxydecanoic acid, abscisic acid, hydroxyoctanic acid), phenolic acids (caffeic acid, salicylic acid) and flavonoids (luteolin, hesperetin, kaempferol, apigenin, 3,7,40-trihydroxyflavone, naringenin, chrysin, fisetin, vitexin, isoorientin and xanthohumol) as revealed in the liquid chromatography-mass spectrometry analysis. The recovered metabolites enhanced the radical scavenging capacity (free radicals and radical cations), reducing power and prostaglandin inhibition in cyclooxygenase assay. The enhancement was evident from the lower effective concentration of EA fractions than in crude honey and the alcohol-based fractions (methanol and butanol) which were used to remove the sugar components in honey.